2014
DOI: 10.5617/jeb.895
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Ratio Method for Urine Conductivity-Invariant Estimation of Bladder Volume

Abstract: Non-invasive estimation of bladder volume could help patients with impaired bladder volume sensation to determine the right moment for catheterisation. Continuous, non-invasive impedance measurement is a promising technology in this scenario, although influences of body posture and unknown urine conductivity limit wide clinical use today. We studied impedance changes related to bladder volume by simulation, in-vitro and in-vivo measurements with pigs. In this work, we present a method to reduce the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…The data presented herein (Table 5) show that for a constant fluid volume significant differences (p < 0.05) in GI values follow conductivity changes. These results are in agreement with previous studies [8], [12], indicating that GI can be used to estimate volumes only when conductivity of the object under study remains constant.…”
Section: Discussionsupporting
confidence: 93%
“…The data presented herein (Table 5) show that for a constant fluid volume significant differences (p < 0.05) in GI values follow conductivity changes. These results are in agreement with previous studies [8], [12], indicating that GI can be used to estimate volumes only when conductivity of the object under study remains constant.…”
Section: Discussionsupporting
confidence: 93%
“…The conductivity of the thin bladder wall was discounted, and the conductivity of the bladder was considered the same as the conductivity of urine. The urine conductivity range aligns with the range of urine conductivities reported in the current literature 24 , 26 28 .…”
Section: Simulation Data Generationsupporting
confidence: 86%
“…They proposed a method based on machine learning by training the measured voltages [3] and the reconstructed EIT images [8] to determine the bladder status. Schlebusch et al found that urine conductivity significantly affects the measurement accuracy of bladder volume by EIT [9]. He et al simulated a planar electrode array to image the bladder in three-dimension (3D), which obtained the information about the bladder location in the third dimension [10].…”
Section: Introductionmentioning
confidence: 99%